KOMPARASI PERATURAN STANDAR MUTU TABIR SURYA YANG DIPERJUALBELIKAN ANTARA KOREA SELATAN DAN INDONESIA - Gabriella Angelina Permatasari, (Universitas Warmadewa, Denpasar, Bali, 2023)
Globalization has brought the beauty trend of having glass skin, which means skin has its smooth, flawless, and seem like glass impacted by K-Wave. In general, consumers buy products related with the composition or products that are being widely discussed by the public. As a tropical country, Indonesian people need sunscreen to minimize the potential risk of skin cancer, especially UV and infrared. The objective of this study is to compare the sunscreen regulations of South Korea and Indonesia in order finds regulation to be implemented. As a juridical-normative research with a comparative, statute, and conceptual approach it will compares sunscreen quality and standards regulations in South Korea and Indonesia using positive law. The research results prove there are some variations in sunscreen product chemical compound. There are 32 ingredients used in Indonesia and around 6 ingredients have different maximum limit or are not applied yet in Korea. Along with this, 6 ingredients has different maximum limit or have not been implemented yet in Indonesia. Apart from that, the regulations between South Korea and Indonesia regarding animal testing for cosmetic products also have differences. In Indonesia, animal welfare is one of the principles held by government to enforce animal rights, while in Korea it's prohibited to distribute the product that exploit animal. There is a urgent need to reform the quality standards of cosmetic in sunscreen products and the animal testing regulation in Indonesia in order to protect consumer rights and enlarge Indonesia's potential growth of selling sunscreen.